Experimental investigation of energy recovery from air conditioning air exchange - Lau, Kai Hang. (2009)
As global warming and energy depletion have become pressing issues to the world, people are more concern about energy conservation. Many green technologies and practices have been created. One practice is energy recovery. In buildings of the modern cities, heat recovery from air ventilation is an important mean of energy conservation. In this project, the student’s aim is to investigate ways and means of recovering energy from cold discharge air in the air-conditioning cycle. Certain existing technologies are introduced briefly in this report. The report will include the design process of the student’s prototype of a plate heat exchanger. Experiments were carried out with the plate heat exchanger to test its operation efficiency. Fans are set up at two entrances of the heat exchanger, flow meter is placed at the exits to measure the flow rates of the two streams of air. Data obtained in experiments is tabulated and compared with theory calculations. The average effectiviness of the heat exchanger in 60% compared to the theory calcualation of 80%. Calculations of energy and cost saved by the heat exchanger are also included in the report.